1997
DOI: 10.1002/(sici)1099-1514(199705/06)18:3<227::aid-oca598>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: A collocation-type method for linear quadratic optimal control problems

Abstract: This communication presents a spectral method for solving time‐varying linear quadratic optimal control problems. Legendre–Gauss–Lobatto nodes are used to construct the mth‐degree polynomial approximation of the state and control variables. The derivative x·(t) of the state vector x(t) is approximaed by the analytic derivative of the corresponding interpolating polynomial. The performance index approximation is based on Gauss–Lobatto integration. The optimal control problem is then transformed into a linear pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…Due to the properties of the orthogonal family of collocation points (such as those found via the Legendre or Chebyshev polynomial basis) approximations converge at spectral rates [6]. The most widely used Legendre PS method [1,5,6,9,10] is based on the LGL points [36]. However, the Legendre PS method may be based upon LGR or LG nodes as well [36,37].…”
Section: Numerical Methods For Optimal Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the properties of the orthogonal family of collocation points (such as those found via the Legendre or Chebyshev polynomial basis) approximations converge at spectral rates [6]. The most widely used Legendre PS method [1,5,6,9,10] is based on the LGL points [36]. However, the Legendre PS method may be based upon LGR or LG nodes as well [36,37].…”
Section: Numerical Methods For Optimal Controlmentioning
confidence: 99%
“…The computational strategy of the GOCM-S is to find the feasible solution x N (t) ∈ X and u N (t) ∈ U for the following cases: 9) subject to the Galerkin constraints…”
Section: Computation Strategy For Gocm-smentioning
confidence: 99%
See 1 more Smart Citation
“…The basic idea of this method is to seek polynomial approximations for the state, costate, and control functions in terms of their values at the Legendre-Gauss-Lobatto (LGL) points. Thus it is apparent that LQR problems can be easily transformed into quadratic programming (QP) problems (a quadratic cost function subject to linear algebraic constraints) [19]. He and Unbehauen [20] compared pseudospectral techniques to Riccati methods in solving LQR problems and showed that there is a huge reduction in the number of equations to be solved, and the required computer memory storage.…”
Section: Introductionmentioning
confidence: 99%
“…He and Unbehauen [20] compared pseudospectral techniques to Riccati methods in solving LQR problems and showed that there is a huge reduction in the number of equations to be solved, and the required computer memory storage. Although [19][20][21][22] solved their QP numerically, the analytical solutions were derived using preudospectral methods as shown in [23]. Compared with other analytical control laws that use step-by-step replacements for the states [24], this approach is quite easy to derive and implement.…”
Section: Introductionmentioning
confidence: 99%